From Leonardo to Picasso (1939–1953): The Masters Who Marked War and Peace in Milan - Colombo, Silvia (Archīum Ateneo, 2024)
This paper intends to highlight the role the arts and the exhibition system had during WWII period in Milan—a strategic centre in the fields of politics, culture and economics. At that time we can notice two main occurrences: the Leonardo exhibition at Palazzo dell’Arte in 1939, and the Picasso solo show at Palazzo Reale in 1953. In the beginning of 1939 the war was more than a threat but, despite that, the fascist regime decided to organize a temporary exhibition dedicated to Leonardo with clear propaganda purposes. After WWII and the defeat of the regime, the public administration of the city was able to arrange a Picasso exhibition and, during a moment of peace-building, the choice of the Spanish master was not accidental. It is clear that exhibition-making here was conceived as a tool for cultural interventions, marking war and peace situations and tracing a political “manifesto”.